Mechanism of Intermittent Theta-Burst Stimulation in Synaptic Pathology in the Prefrontal Cortex in an Antidepressant-Resistant Depression Rat Model. (9th September 2020) - Lee, Chi-Wei; Wu, Han-Fang; Chu, Ming-Chia; Chung, Yueh-Jung; Mao, Wei-Chang; Li, Cheng-Ta; Lin, Hui-Ching
Abstract: Intermittent theta-burst stimulation (iTBS), a form of repetitive transcranial magnetic stimulation, is considered a potential therapy for treatment-resistant depression. The synaptic mechanism of iTBS has long been known to be an effective method to induce long-term potentiation (LTP)-like plasticity in humans. However, there is limited evidence as to whether the antidepressant effect of iTBS is associated with change in synaptic function in the prefrontal cortex (PFC) in preclinical study. Hence, we applied an antidepressant (i.e., fluoxetine)-resistant depression rat model induced by severe foot-shocks to investigate the antidepressant efficacy of iTBS in the synaptic pathology. The results showed that iTBS treatment improved not only the impaired LTP, but also the aberrant long-term depression in the PFC of antidepressant-resistant depression model rats. Moreover, the mechanism of LTP improvement by iTBS involved downstream molecules of brain-derived neurotrophic factor, while the mechanism of long-term depression improvement by iTBS involved downstream molecules of proBDNF. The aberrant spine morphology was also improved by iTBS treatment. This study demonstrated that the mechanism of the iTBS paradigm is complex and may regulate not only excitatory but also inhibitory synaptic effects in the PFC.